Association of blood lipid levels with mild cognitive impairment in the elderly: community-based case-control study in Tianjin city - Ke-shan LIU; Li-ping ZHU; Xiao-min WU (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo explore the relationship between blood lipid and the risk of mild cognitive impairment (MCI) among community elderly for providing evidence to MCI prevention in the population. MethodsA case-control study was conducted among residents aged 65 years and above in four communities of Tianjin city during March 2016. The cases were 210 MCI patients diagnosed while attending physical examination at community healthcare centers; the controls were 1 : 1 gender- and age (± 1 year)-matched residents with normal cognitive ability. Face-to-face questionnaire interview, physical examination and laboratory detections were carried out among the participants. Diagnostic and Statistical Manual of Mental Disorders-V (DSM-V) was adopted in diagnosis and assessment of MCI. Multivariate conditional logistic regression analysis was used to explore the relationship between blood lipid and MCI in the elderly. ResultsNo significant differences between the cases and controls were detected in total cholesterol (TC: 186.50 [25th, 75th percentile: 160.75, 215.00] vs. 195.50 [168.00, 217.25] mg/dL), low density lipoprotein-cholesterol (LDL-C: 101.00 [77.75, 121.00] vs. 100.00 [79.75, 123.00] mg/dL), high density lipoprotein-cholesterol (HDL-C: 58.50 [46.75, 71.25] vs. 58.00 [47.00, 70.00] mg/dL), and LDL-C/HDL-C (1.71 [1.30, 2.35] vs. 1.66 [1.31, 2.26]) (P > 0.05 for all). The results of conditional multivariate logistic regression analysis showed that after adjusting for education, hypertension, diabetes, heart disease, and stroke, the LDL-C (mg/dL) of higher than 100 was associated with increased risk of MCI (100 - 130: odds ratio [OR] = 2.37, 95% confidence interval [CI]: 1.21 - 4.65; 130 - 160: OR = 3.22, 95% CI: 1.09 - 9.49; > 160: OR = 9.33, 95% CI: 1.59 - 54.61); while, following factors were correlated to decreased risk of MCI: higher TC (200 - 240 vs. < 200 mg/dL: OR = 0.52, 95% CI: 0.27 - 0.99), higher HDL-C (> 40 vs. ≤ 40 mg/dL: OR = 0.30, 95% CI: 0.14 - 0.67), and higher ratio of LDL-C/HDL-C (> 2.30 vs. < 1.31: OR = 0.37, 95% CI: 0.16 - 0.88). ConclusionHigher serum LDL-C is a risk factor of MCI but higher serum HDL-C, LDL-C/HDL-C ratio and moderate TC are protective factors against MCI for community elderly in Tianjin city.